Inclusion and integration. Alternative or correlated models of organization? - Curatola, Annamaria (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2017)
In current educational and social practices it has been widely affirmed the policy of implementing operability based on sound pedagogical principles used with the hiring of a coherent prospect of success. An operation whose level of success, in terms not only quantitative but also qualitative, appears closely linked to the respect of systematic constraints, with the adoption of action models adaptable to the multiplicity and diversity of contexts of reference, with the foresight to systematically monitor and critic of its development, with the wealth of collaborative convergence and last but not least, the sustainability of its materialize with really available means. The organizational and management models of that practice are effective representation in two basic concepts, including their relatively dissimilar: that of “integration” and that of "inclusion”. Both certainly effective, but that give rise to each specific application, especially on the organizational and management level, but also on that of prospection outcomes. Unfortunately, the sense of their meaning is not always clear, so much so that often are conceived in terms of synonymy with the effects certainly limiting for the same quality of services (educational and social) in place. Hence the need to dwell, albeit in an essential way, the respective meanings, on the principles that underlie them and their real usefulness.